1995
DOI: 10.1126/science.270.5240.1326
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of ERK and JNK-p38 MAP Kinases on Apoptosis

Abstract: Apoptosis plays an important role during neuronal development, and defects in apoptosis may underlie various neurodegenerative disorders. To characterize molecular mechanisms that regulate neuronal apoptosis, the contributions to cell death of mitogen-activated protein (MAP) kinase family members, including ERK (extracellular signal-regulated kinase), JNK (c-JUN NH2-terminal protein kinase), and p38, were examined after withdrawal of nerve growth factor (NGF) from rat PC-12 pheochromocytoma cells. NGF withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

235
3,947
27
26

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,072 publications
(4,235 citation statements)
references
References 76 publications
235
3,947
27
26
Order By: Relevance
“…Concurrent activation of SAPK or p38 together with inhibition of Erks seem to be necessary for apoptosis following NGF withdrawal (Xia et al, 1995 (Figure 2a, upper panel).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent activation of SAPK or p38 together with inhibition of Erks seem to be necessary for apoptosis following NGF withdrawal (Xia et al, 1995 (Figure 2a, upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…However, two signalling pathways have recently been implicated in survival signalling by tyrosine kinase receptors: the classic Raf/MAPK pathway in the PC12 cell system (Xia et al, 1995) and the PI3-kinase pathway in PC12 cells and in ®broblasts Cooper, 1995, 1996). Both, the MAPK and the PI3-kinase pathways seem to be required for IGF-I to inhibit apoptosis of di erentiated PC12 cells following NGF withdrawal (Parrizas et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several groups have also reported that activation of the JNK/SAPK pathway can also induce cell death. For example, activation of JNK/SAPK in the absence of ERK activity induces apoptosis in neural cells (Xia et al, 1995). Furthermore, expression of MEKK1, an upstream activator of JNK/SAPK results in the apoptotic death of ®broblasts , suggesting that under some circumstances, JNK/SAPK signalling alone may be su cient to cause cell death.…”
Section: Discussionmentioning
confidence: 99%
“…c-jun luciferase activity Cerebellar granule neurons were transfected on the fifth day of culture (day in vitro (DIV) 5) by a modified calcium phosphate protocol (Xia et al 1995). Cells were washed with K25 ) S and calcium phosphate/DNA complexes were added to neurons for 1 h. Neurons were then washed twice with K25 ) S and restored to K25 + S medium.…”
Section: Immunoblottingmentioning
confidence: 99%